2008
DOI: 10.1073/pnas.0805514105
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC2 blockade by nitric oxide and histone deacetylase inhibitors reveals a common target in Duchenne muscular dystrophy treatment

Abstract: The overlapping histological and biochemical features underlying the beneficial effect of deacetylase inhibitors and NO donors in dystrophic muscles suggest an unanticipated molecular link among dystrophin, NO signaling, and the histone deacetylases (HDACs). Higher global deacetylase activity and selective increased expression of the class I histone deacetylase HDAC2 were detected in muscles of dystrophin-deficient MDX mice. In vitro and in vivo siRNA-mediated down-regulation of HDAC2 in dystrophic muscles was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
224
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 240 publications
(233 citation statements)
references
References 30 publications
7
224
0
2
Order By: Relevance
“…Our results concur with a recent mass spectrometry survey (42), which found HDAC1 and -2, but not HDAC8, among 417 cellular proteins modified by 100 M 4HNE (43). HDAC2 can also be nitrosylated at Cys 262 and Cys 274 (44,45). Because residues sensitive to ROS and reactive nitrogen species are often sensitive to modification by RCS, our results suggest that the homologous cysteine residues in HDAC1 and HDAC3 as well as yeast RPD3 could be sensitive to nitrosylation and oxidation.…”
Section: Discussionmentioning
confidence: 73%
“…Our results concur with a recent mass spectrometry survey (42), which found HDAC1 and -2, but not HDAC8, among 417 cellular proteins modified by 100 M 4HNE (43). HDAC2 can also be nitrosylated at Cys 262 and Cys 274 (44,45). Because residues sensitive to ROS and reactive nitrogen species are often sensitive to modification by RCS, our results suggest that the homologous cysteine residues in HDAC1 and HDAC3 as well as yeast RPD3 could be sensitive to nitrosylation and oxidation.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, the extent to which HDACi ameliorate the mdx phenotype varies significantly among these compounds, with trichostatin A (TSA) being the most effective drug at defined concentrations (TSA 0.6 mg/kg, delivered by daily intraperitoneal injection). An interesting insight into the specific role of individual HDACs in the pathogenesis of muscular dystrophy is suggested by the comparable efficacy of MS275, which selectively inhibits class I HDACs, and pan HDACi, which inhibit both class I and II HDACs (6,7). This suggests that inhibition of class I HDACs is sufficient to exert most of the beneficial effects observed in HDACi-treated mdx mice, once again emphasizing the key contribution to DMD pathogenesis by class I HDACs.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the effectiveness of histone deacetylase inhibitors (HDACi) in the treatment of muscular dystrophies, using mdx mice as models (6,7). The mdx mice are the mouse model of human DMD and therefore provide the most amenable and approachable disease model for exploratory and preclinical evaluation of experimental interventions in muscular dystrophies.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work described that mdx mice have an altered HDAC/HAT functional balance (8,16,17). Additional studies revealed that, in mdx heart, Cx43 is predominantly lateralized, a condition that correlates with the presence of oxidative stress (9) and alterations in the propagation of cardiac electrical impulses (18).…”
mentioning
confidence: 98%